Pengaruh Strategi Promosi Dan Kualitas Pelayanan Terhadap Volume Penjualan Pada Nandini Jungle Resort & Spa Di Payangan - I Wayan Astawa; Ni Komang Erik Yuliani (Jurnal Sains Terapan Pariwisata, 2021)
The purpose of this study was to determine the effect of promotion strategies and service quality on sales volume at Nandini Jungle Resort & Spa in Payangan. The sample used was 50 customers. The data sources used were primary and secondary data. Data were analyzed using the SPSS computer program. Methods of data collection using observation, questionnaires and documentation study. The data analysis technique used multiple linear regression analysis. The results obtained from the results of statistical analysis show that partially the promotion strategy variable (X1) has no significant effect with the -t test results of 0.071 with sig 0.944 on sales volume (Y) and the variable service quality (X2) has a positive and significant effect. t-test result of 8,731 with sig 0,000 on sales volume (Y). Meanwhile, simultaneously it shows that the magnitude of the influence of promotional strategies and service quality on sales volume is 42.151 and sig 0.000 with hypothesis testing using the f-test, with the results of the promotional strategy variable (X1) and service quality (X2) on sales volume (Y) having a positive effect. and significant at Nandini Jungle Resort & Spa in Payangan.